(untitled) (International Journal of Engineering and Computer Science, 2013)
Speech is the medium through which human beings can communicate. Segmentation of speech is required for better speech recognition. Segmentation of speech can be done into basic units like words, phonemes or syllables. The two main methods used for segmentation of speech signals are manual segmentation and automatic segmentation. But manual segmentation is not favoured as it is tedious, time consuming and results are not reproducible. So, automatic segmentation is used for segmentation of speech. This paper describes a number of methods for automatic segmentation of speech into units like phonemes or Syllables.